Evolution of conservation approaches: embracing a people focus approach (Antropología. Revista interdisciplinaria del INAH, 2023)
Conservation principles originated in the mid-19th century in Europe has been acting as the core of the discourse with specific practical approaches for protecting the material remains of the past with much emphasis on their aesthetic and historical values. These principles, which originated with views expressed by individuals or smaller groups, have evolved over the last one and half centuries. This paper briefly explores the evolution of approaches looking at three interconnected but distinct periods: pre-1970 (fabric-focused period); 1960-1990 (transition period); post-1990 (people-focused period). It argues that evolution has addressed many gaps and deficiencies inherited during the early phases of the discourse. One such gap was the heavy focus on materiality by overlooking people-centric values of heritage (including potential contributions to the livelihood). The paper demonstrates that the people factor gained a more prominent role during the post-1990 phase, emphasising the development of a people-focused approach to conservation. This entails placing people at the heart of the heritage discourse, thus focusing on sustaining heritage, as well as its contributions to sustain the society at large.